Dysregulated miR-142, -33b and -423 in granulosa cells target TGFBR1 and SMAD7: a possible role in polycystic ovary syndrome. (10th July 2019) - Li, Yan; Xiang, Yungai; Song, Yuxia; Wan, Lijing; Yu, Guo; Tan, Li
Abstract: It is well established that microRNA (miRNA) expression profiles are altered in patients with polycystic ovary syndrome (PCOS). In addition, abnormal transforming growth factor beta (TGFB) signaling in granulosa cells is related to the pathological conditions of PCOS. However, the function of dysregulated miRNAs in PCOS is still unclear. In this study, we aimed to elucidate the roles of specific miRNAs in PCOS. We collected follicular fluid from 46 patients with PCOS and 32 healthy controls. Granulosa cells (GCs) were separated and the levels of six candidate miRNAs were determined by quantitative RT-PCR. The direct targets of three dysregulated miRNAs were predicted using bioinformatic tools and confirmed using a dual luciferase assay and immunoblotting. The biological function of three dysregulated miRNAs in primary GCs was determined using a cell proliferation assay and flow cytometry. We found that miR-423 expression was downregulated ( P = 0.038), and the levels of miR-33b ( P = 0.032) and miR-142 ( P = 0.021) were upregulated in GCs from patients with PCOS, compared to controls. miR-423 directly repressed SMAD family member 7 ( SMAD7 ) expression, while transforming growth factor beta receptor 1 ( TGFBR1 ) was a direct target of both miR-33b and miR-142. An RNA oligonucleotide mixture containing miR-423 inhibitor, miR-33b mimic, and miR-142 mimic repressed TGFB signaling, promoted cell proliferation ( P = 0.0098), repressed apoptosis ( P = 0.027), and increased S phase cell numbers ( P = 0.0036) in primary cultures of GCs, compared to the cells treated with a sequence scrambled control RNA oligonucleotide. This study unveiled the possible roles of three miRNAs in PCOS and might provide candidate biomarkers for PCOS diagnosis while in vivo functional studies, using transgenic or knockout mouse models, are expected to confirm the roles of dysregulated miRNAs in the pathogenesis of PCOS.